2013
DOI: 10.1088/2043-6262/4/2/025005
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation in polyvinyl alcohol–polypyrrole–multiwall carbon nanotube composites below room temperature

Abstract: Polyvinyl alcohol–polypyrrole–multiwall carbon nanotube composite polymer films have been synthesized by a chemical oxidative polymerization technique. Dielectric properties have been measured in the frequency range from 20 Hz to 1 MHz and in the temperature range 77 ⩽ T ⩽  300 K. Electric modulus vector analysis gives the presence of dielectric relaxation peaks for different composites from which the activation energies have been calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The ease of preparation processes of polymer composites and the diverse range of applications are the driving force of continuous research in this arena. Another aspect of studying the polymer nanocomposite and polymer blend is the quest to understand the rich and intriguing physics of these complex systems [7][8][9][10][11][12][13][14]. If we can vary the property systematically by controlling the filler content into the matrix, it will surely open up new avenues of applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ease of preparation processes of polymer composites and the diverse range of applications are the driving force of continuous research in this arena. Another aspect of studying the polymer nanocomposite and polymer blend is the quest to understand the rich and intriguing physics of these complex systems [7][8][9][10][11][12][13][14]. If we can vary the property systematically by controlling the filler content into the matrix, it will surely open up new avenues of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in the values of dc conductivity and effective permittivity with increasing loading of Ag particles were reported by Mahendia et al [34]. Polyvinyl alcohol-carbon nanotube (CNT) based composites have also been reported to be promising materials having interesting magneto transport properties [1,7,9]. Apart from these, electrical properties of PVA/ Barium Zirconium Titanate polymer ceramic composites [35] and polymer -Sr modified Barium Zirconium Titanate ceramic has also been studied by Senthil et al [36].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement variance was a maximum at 0.1 and 0.2 wt % MWCNTs loading, indicating that the amount of MWCNT was insufficient for the formation of a network in the composite films while the MWCNT content was less than 0.1 wt %. However, with an increasing content of MWCNT in the PEDOT matrix, more and more networks are formed, resulting in a sharp increase in the conductivity of the composites . These observations indicated that the percolation threshold of the nanocomposite film was between 0.1 and 0.3 wt % MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric parameter as a function of frequency is described by the complex permittivity in the form [1] e à ðvÞ ¼ e 0 ðvÞ À ie 00 ðvÞ; ð2Þ…”
Section: Dielectric Relaxation Studiesmentioning
confidence: 99%